Sustainable entrepreneurship: Comparing the determinants of entrepreneurial self-efficacy and social entrepreneurial self-efficacy - Broccia, S.; Dias, Á.; Pereira, L. (Social Sciences, 2022)
Sustainable entrepreneurship creates value beyond profit. Its role is increasingly important in addressing issues related to environmental challenges. Sustainable entrepreneurs represent a tool to attain the Sustainable Development Goals established by the United Nations that address climate change, social inequality, human rights, and economic development. To solve these challenges, there is a need for high-performing sustainable entrepreneurs. The roles of innovativeness, organizational capabilities, and philanthropic corporate social responsibility (CSR) in the performance of sustainable entrepreneurs are still underexplored. Hence, this study proposes an analysis of the indirect and direct effects of innovativeness on entrepreneurial self-efficacy (ESE) and social entrepreneurial self-efficacy (SESE) and of the mediating role of organizational capabilities and philanthropic CSR. Based on structural equation modeling and importance-performance matrix analysis, the findings from a survey of 116 sustainable entrepreneurs identified a positive relationship between innovativeness and ESE, organizational capabilities, and philanthropic CSR. The indirect relationship mediated by organizational capabilities was found to be positive, while for philanthropic CSR, it was positive for SESE but negative for ESE. Interestingly, it was found that SESE is only positively influenced in indirect relations. This study contributes to the literature on how innovativeness can promote ESE and SESE and the role of organizational capabilities and philanthropic CSR in enhancing performance among sustainable entrepreneurs.